2000
DOI: 10.1002/1098-237x(200009)84:5<658::aid-sce6>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Development of knowledge about electricity and magnetism during a visit to a science museum and related post-visit activities

Abstract: This article reports on part of a larger study of how 11‐ and 12‐year‐old students construct knowledge about electricity and magnetism by drawing on aspects of their experiences during the course of a school visit to an interactive science museum and subsequent classroom activities linked to the science museum exhibits. The significance of this study is that it focuses on an aspect of school visits to informal learning centers that has been neglected by researchers in the past, namely the influence of post‐vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
15

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 178 publications
(113 citation statements)
references
References 17 publications
2
96
0
15
Order By: Relevance
“…This confirms previous research on the importance of classroom pre-and posttrip learning (see, e.g., Anderson, Lucas, Ginns, & Dierking, 2000;Falk & Dierking, 1992). The results from this study suggest, at least in these two cases, that classroom teachers have an important role in shaping their students' trip experiences, not only what students do, but how they view the trip, what they value and focus on, what they see as the purpose of the trip, and what they remember about it.…”
Section: Discussionsupporting
confidence: 92%
“…This confirms previous research on the importance of classroom pre-and posttrip learning (see, e.g., Anderson, Lucas, Ginns, & Dierking, 2000;Falk & Dierking, 1992). The results from this study suggest, at least in these two cases, that classroom teachers have an important role in shaping their students' trip experiences, not only what students do, but how they view the trip, what they value and focus on, what they see as the purpose of the trip, and what they remember about it.…”
Section: Discussionsupporting
confidence: 92%
“…promotes student motivation (S. Hidi, Weiss, Berndorff, & Nolan, 1998;Paris, Yambor, & Packard, 1998) and learning (Cox-Petersen, Marsh, Kisiel, & Melber, 2003;Mortensen & Smart, 2007;Tofield, et al, 2003). Educational impact is increased by post-visit activities (D. Anderson, et al, 2000;Davidson, et al, 2010;Griffin, 1994). In the present study, the students participated in pre-trip preparation activities supplied by their teacher and were engaged in field trip laboratory work.…”
Section: Discussionmentioning
confidence: 78%
“…advance content preparation, active participation in structured science activities, and follow-up activities (National Research Council, 2009). Recent research has shown that advance field trip preparation gives students a framework which guides what they should pay attention to during the visit and how they should interpret what they see (D. Anderson, Kisiel, & Storksdieck, 2006;D. Anderson, Lucas, Ginns, & Dierking, 2000;Griffin & Symington, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies that reported about meaningful preparation or follow-up activities described research settings, in which the researchers were involved in preparing the activity with the teachers or the museum staff (Anderson et al, 2000;Gilbert & Priest, 1997;Henriksen & Jorde, 2001). In a recent review of the research on school visits to museums, Griffin (2004) provides many possible reasons for this pattern.…”
Section: Theoretical Backgroundmentioning
confidence: 99%